Analisis Kinerja Keuangan pada PT. Bank Sinarmas Tbk yang Terdaftar pada Bursa Efek Indonesia Tahun 2019 – 2023 - Berkat Febrianto Lase; Pustika Ayuning Puri; Wahyu Purbo Santoso (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The strategic role of banking as an intermediary institution manifests through its ability to gather and channel funds from the public to support economic activities, ultimately enhancing the stability of the country's economic structure. The importance of banking health in the fund collection process requires a sound condition and banking services that attract public interest. Bank health evaluation can be conducted through various methods, including the CAMEL method covering capital, asset quality, management, earnings, and liquidity, as well as the RGEC method encompassing Risk Profile, Good Corporate Governance, Earnings, and Capital. Bank Sinarmas, as one of the public banks in Indonesia, has played a significant role in economic recovery through the distribution of People's Business Credit (KUR) and its success in maintaining the health of the banking sector. This research is descriptive with a quantitative approach, utilizing literature review and documentation as data collection techniques. The results of this study indicate that the financial condition of PT Bank Sinarmas Tbk from 2019 to 2023 can be classified as generally “healthy”. However, in terms of Asset Quality and Management aspects, it falls into the "Fairly Healthy" category, while in terms of Profitability, specifically the Return on Asset (ROA) ratio, it is categorized as "Less Healthy." The findings are expected to serve as a guide for the company, assisting in maintaining a healthy financial state and improving areas that are less healthy to uphold public trust. The research contributes to academic literature, serving as a significant reference for the development of financial management knowledge, particularly in the analysis of financial statements. It is also envisioned as a foundation for further research with similar focuses. As guidance for future researchers, it is recommended to broaden the scope of research by involving other financial ratio indicators, following the latest methods in accordance with the regulatory framework of financial institution supervision in Indonesia.